Role of the IL-33-ST2 axis in sepsis. Issue 1 (December 2017) - Xu, Hui; Turnquist, Heth; Hoffman, Rosemary; Billiar, Timothy
Abstract Sepsis remains a major clinical problem with high morbidity and mortality. As new inflammatory mediators are characterized, it is important to understand their roles in sepsis. Interleukin 33 (IL-33) is a recently described member of the IL-1 family that is widely expressed in cells of barrier tissues. Upon tissue damage, IL-33 is released as an alarmin and activates various types of cells of both the innate and adaptive immune system through binding to the ST2/IL-1 receptor accessory protein complex. IL-33 has apparent pleiotropic functions in many disease models, with its actions strongly shaped by the local microenvironment. Recent studies have established a role for the IL-33-ST2 axis in the initiation and perpetuation of inflammation during endotoxemia, but its roles in sepsis appear to be organism and model dependent. In this review, we focus on the recent advances in understanding the role of the IL-33/ST2 axis in sepsis.